2019
DOI: 10.1089/aivt.2019.0001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Subcytotoxic Exposure of Silver Nanoparticles on Osteogenic Differentiation of Human Bone Marrow Stem Cells

Abstract: Introduction: In vitro toxicology evaluations utilizing human stem cell models represent attractive alternatives to conventional animal models, which are not always predictive of human responses. Silver nanoparticles (AgNP) are a potent antimicrobial for use in orthopedic devices. However, AgNP exposure may alter the behavior of stem cells within the bone marrow. The aim of this study was to determine if differences in cell proliferation, early, and late osteogenic differentiation markers can be detected in os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Hydrogels are interesting materials for stem cell growth in regenerative medicine. Furthermore, the presence of AgNPs is known to be beneficial to osteogenic differentiation of human mesenchymal stem cells. Hydrogels incorporating AgNPs may therefore be promising materials in bone tissue engineering and for the fabrication of orthopedic implants.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogels are interesting materials for stem cell growth in regenerative medicine. Furthermore, the presence of AgNPs is known to be beneficial to osteogenic differentiation of human mesenchymal stem cells. Hydrogels incorporating AgNPs may therefore be promising materials in bone tissue engineering and for the fabrication of orthopedic implants.…”
Section: Resultsmentioning
confidence: 99%
“…Silver is favored in bone tissue engineering because of its antibacterial characteristics, but numerous studies have shown that it also inhibits mesenchymal stem cell (MSCs) proliferation ( Nguyen et al, 2019 ). The fundamental analysis to determine a nanomaterial’s biocompatibility is its assessment of proliferation.…”
Section: Current Developments Of Nanotechnology In Orthopedic Implantsmentioning
confidence: 99%
“…[24,[52][53][54][55] According to the report of Alexander K et al, a cytotoxic threshold of 10 μg mL −1 PVPcoated 10 nm AgNPs exists for hBMSCs, and even a single 24-h exposure during the 21-day culture period can result in impaired osteocyte function. [56] The study conducted by Jia et al demonstrated that 20 nm AgNPs exhibit cytotoxicity toward colon cells, resulting in a reduction in cell viability at concentrations greater than 15 μg mL −1 . [57] To advance the development of silver-containing materials with enhanced biocompatibility for medical use, there is an urgent need for systematic investigation into their potential cytotoxicity.…”
Section: Cytotoxicity Of Silver and Bacterial Resistance To Silvermentioning
confidence: 99%
“…[ 24,52–55 ] According to the report of Alexander K et al., a cytotoxic threshold of 10 µg mL −1 PVP‐coated 10 nm AgNPs exists for hBMSCs, and even a single 24‐h exposure during the 21‐day culture period can result in impaired osteocyte function. [ 56 ] The study conducted by Jia et al. demonstrated that 20 nm AgNPs exhibit cytotoxicity toward colon cells, resulting in a reduction in cell viability at concentrations greater than 15 µg mL −1 .…”
Section: Introductionmentioning
confidence: 99%